1995
DOI: 10.1159/000178965
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Reflection Spectrophotometry: Spatial and Temporal Variation of Hb Oxygenation in Human Skin

Abstract: Applying a fast scanning reflection spectrophotometer and multicomponent spectra analysis, oxygen saturation (SHb) and relative concentration (CHb) of hemoglobin in the skin were determined at eight skin sites in 11 healthy persons. SHb was significantly higher at the tip of the index finger and big toe (90 ± 3.9 and 92 ± 4.2%, respectively) compared with the forehead, volar forearm, back of hand, abdomen, calf and forefoot where mean values varied between 52 and 67% (p < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 10 publications
(14 reference statements)
4
7
0
Order By: Relevance
“…This is followed by mean StO2 of 84.8 0.9%  for detection distance of 50 mm. These values are comparable to that observed in the works of previous researchers who used different analytical model namely Kubelka Munk [14] and Cumulant based forward model (CM) [15,16]. The results in Table 1 and Figure 3 also revealed small standard deviation among these subjects, indicating good repeatability of the analytical technique and the proposed experimental method when the imaged skin site is of close proximity to the detection system (<50 mm).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This is followed by mean StO2 of 84.8 0.9%  for detection distance of 50 mm. These values are comparable to that observed in the works of previous researchers who used different analytical model namely Kubelka Munk [14] and Cumulant based forward model (CM) [15,16]. The results in Table 1 and Figure 3 also revealed small standard deviation among these subjects, indicating good repeatability of the analytical technique and the proposed experimental method when the imaged skin site is of close proximity to the detection system (<50 mm).…”
Section: Resultssupporting
confidence: 86%
“…posterior forearm, leg). This is contributed by the presence of arteriovenous anastomoses (AVAs) which can be found in abundance in the acral skin site [14]. The AVAs provide circulatory connection between the artery and veins and also produce shunting of oxygenated arterial blood into the venous compartment during muscle relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…4, the mean of S m O 2 estimated for the fingertip and the back of hand of the employed human subjects at rest condition, and the heated fingertips are given by 92.6±3.7%, 39.8±6.85% and 102±3.1%, respectively. The high S m O 2 value of 92.6±3.7% observed for the fingertip of volunteers at rest agreed well with the oxygen saturation value of 92±2.6% reported by Caspary et al [11] who also conducted the similar experiment. This is due to the presence of Arteriovenous anastomoses (AVAs) that are available in abundance in acral (fingertip) than non-acral skin (back of the hand) [12].…”
Section: Discussionsupporting
confidence: 90%
“…For human skin at different measuring sites, at a given skin temperature, the tip of the index finger showed the highest hemoglobin concentrations which could be related to the tissue blood volume. 8 Our own measurements showed that the human lip was an even better test location for the same reasons (see Figure 3). In Figure 3(a) the diffuse reflectance spectra of different skin tissues are presented, which are dominated by the absorption features of oxygenated hemoglobin (hemoglobin oxygenation saturation, HbSO 2 , is usually high at around 90%).…”
Section: Glucose In Blood and Tissuementioning
confidence: 77%